Modelagem matemática nas atividades de estágio: saberes revelados por futuros professores - Almeida, Rafael Neves (2009)
Based on the assumption that supervised internship is an important part of a teacher s education, this work sought to identify what are the possible relations/influences of mathematical modeling on the internship activities of a future mathematics teacher. A qualitative research was carried out in a public state school in the city of São Carlos and included the participation of two students of an Undergraduate Mathematics course (Teaching License). While these students were attending the subject Supervised Internship in Mathematics in Elementary Education 2, they joined the author of this research to design three projects of mathematical modeling for seventh-grade students. In the case study, the trainee teachers applied all the three projects, what resulted in an empirical material consisted of audio interviews with the trainee teachers, videos of the classes, documents produced by the seventh-grade students, and documents produced by the trainee teachers (field journals, reflective journals, and reports of the internship). The theoretical basis included works by Tardif (2002) and Mizukami (2004) for understanding how the teacher learning takes place, as well as works by Moura (1999) and Pimenta (2004), which contributed to the understanding of the supervised internship as an environment of teacher knowledge, while the studies by Borba (1999), Biembengut (1999) and Barbosa (2001c) allowed the construction of a concept on the use of mathematical modeling in Mathematics teaching. The focus of investigation was the way the trainee teachers acted in the supervised internship while developing projects of mathematical modeling. The idea was to analyze which types of knowledge, conflicts, and reflections they build in such process. The research showed both the potential of mathematical modeling being used in initial education as part of internship activities when undergraduates take their chances on their first experiences as teachers and the production of teacher knowledge.